Bovine bilateral mesenchymal hamartomas on the upper eyelid: A case report - Eroksuz, Yesari; Polat, Eren; Incili, Canan Akdeniz; Karabulut, Burak; Eroksuz, Hatice (Czech Academy Agricultural Sciences, 2021)
A 2-day-old calf was presented with a bilateral mass in the medial canthus of the upper eyelid. The masses were removed surgically. The morphological diagnosis was a bilateral hamartoma characterised by an abnormal mixture of tissue indigenous to that area including blood vessels, striated muscle bundles, adipose tissue, isolated cartilage and nerve bundles. No recurrence developed in the 6 months following the surgical removal. Overall, although this congenital defect is relatively rare, it should be differentiated from eyelid tumours such as haemangiomas, squamous cell carcinomas, Meibomian gland tumours, dermoid cysts and teratomas in cattle.
Keywords: calf; congenital malformation; ocular